2008
DOI: 10.1152/ajpgi.90283.2008
|View full text |Cite
|
Sign up to set email alerts
|

Increased expression of the urokinase plasminogen activator system by Helicobacter pylori in gastric epithelial cells

Abstract: Kenny S, Duval C, Sammut SJ, Steele I, Pritchard DM, Atherton JC, Argent RH, Dimaline R, Dockray GJ, Varro A. Increased expression of the urokinase plasminogen activator system by Helicobacter pylori in gastric epithelial cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
39
1
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(47 citation statements)
references
References 59 publications
(82 reference statements)
6
39
1
1
Order By: Relevance
“…In addition to the physiological mechanisms by which gut signals influence food intake, it is also clear that interactions between the gut microbiota and immune and nervous systems can profoundly influence energy balance. We now report that PAI-1, which is increased in plasma in obesity (5, 6), and in stomach with Helicobacter infection (3, 4), acts as a gastric factor suppressing satiety signals. Specifically, the data suggest that PAI-1 suppresses gut-brain signaling by CCK, thereby increasing food intake.…”
Section: Discussionmentioning
confidence: 76%
See 3 more Smart Citations
“…In addition to the physiological mechanisms by which gut signals influence food intake, it is also clear that interactions between the gut microbiota and immune and nervous systems can profoundly influence energy balance. We now report that PAI-1, which is increased in plasma in obesity (5, 6), and in stomach with Helicobacter infection (3, 4), acts as a gastric factor suppressing satiety signals. Specifically, the data suggest that PAI-1 suppresses gut-brain signaling by CCK, thereby increasing food intake.…”
Section: Discussionmentioning
confidence: 76%
“…Because Helicobacter infection increases gastric PAI-1 (3), we then examined food intake in H. felis -infected C57BL/6, PAI-1-H/Kβ, and PAI-1 −/− mice. Confirming previous findings, PAI-1 mRNA was approximately 2-fold higher in the gastric corpus of infected compared with control mice (100 ± 3 vs 206 ± 18, P < .05).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Several in vitro studies have found that the expression of uPAR is upregulated in cancer and gastric epithelial cell lines when co-cultured with H. pylori (Guillemin, Salama, Tompkins, & Falkow, 2002;Sepulveda et al, 2002;El-Etr, Mueller, Tompkins, Falkow, & Merrell, 2004;Iwamoto et al, 2005;Kim et al, 2005;Kim et al, 2007;Iwamoto, Mizokami, Takahashi, Matsuoka, & Matsuzaki, 2008). This phenomenon has also been documented in vivo, specifically in non-neoplastic tissue (adjacent to the tumor growth) obtained from GC patients (Alpízar-Alpízar et al, 2010), as well as in gastric biopsies from patients that have no cancer but are infected with the bacterium (Kenny et al, 2008). In addition, one study reported a significant correlation between uPAR expression in neoplastic tissue and presence of H. pylori in adjacent non-neoplastic tissue (Beyer et al, 2006).…”
Section: Plasminogen Activation System and Helicobacter Pylorimentioning
confidence: 82%